(untitled) (Global Journal of Human-Social Science, 2020)
a. Harold Stassen likened government to fire. As long as it stays within boundaries set by the people, it is a positive factor in their lives. However when it sets its own limits, it is like a fire out of control goes to excess and consumes everything it can including everything that supports it and finally, itself. b. Conversely, a source of sick comedy to image-conscious insiders is an administrator who insists on abiding by and enforcing written rules and laws.